Karst Groundwater Contamination and Public Health Beyond Case Studies (Advances in Karst Science,, 2018)
This book sheds new light on contaminant transport in karst aquifers and the public health implications of contaminated karst groundwater. The papers included were presented at a conference held in early 2016 in San Juan, Puerto Rico, and range from lengthy reviews on contaminant transport mechanisms to short articles summarizing research findings. The conference addressed a variety of topics, such as contamination sources, the hydrogeology of contaminant transport, the storage and release of contaminants, and the health impacts as well as the epidemiology of contaminated water supplies drawn from karst aquifers, and gathered perspectives from experts in different disciplines, including hydrogeologists and public health specialists. Although there is a wealth of literature on specific instances of karst groundwater contamination, this book offers an integrated conceptual framework for the public health impacts of karst groundwater, making it a valuable resource for a broad interdisciplinary readership.